Hegemoni Ideologi Penguasa Terhadap Guru Pendidikan Kewarganegaraan - Zulkarnain (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2020)
This paper wishes to conduct a critical analysis of Citizenship Education in Singapore. Citizenship education as one of the national agenda in Singapore has an important position in providing citizenship understanding in order to prepare young citizens for the future of Singapore. Singapore's centralized education system and strict controls lead to highly vulnerable citizenship education politicization and ideologization of citizens through education. In fact, many studies show that the government under the People's Action party (PAP) is using authoritarian ways to defend and perpetuate its power through education. The attempts by the Singapore government with the soft authoritarian government or some experts say authoritarian with the usual Gramscian meaning